Trends and Determinants of Family Planning Utilization Among Men in Indonesia - Haerawati Idris; Willyana Syafriyanti (Makara Journal of Health Research, 2021)
Background: Population growth rate in the world is still increasing. To control population growth, governments issue family planning programs for married women and men. However, contraception use is still dominated by women. This study aims to analyze the trends and determinants of family planning utilization among men in Indonesia.